Cities and Climate Challenges in Southeast Asia - Seah, Sharon; Qiu, Jiahui; Martinus, Melinda (Book collections on Project MUSE., 2023)
The Climate Change in Southeast Asia Workshop and Compendium Series is a platform to facilitate and promote research on climate-related issues in the Southeast Asian region. Organized by the Climate Change in Southeast Asia Programme at the ISEAS - Yusof Ishak Institute, the objective of this platform is to facilitate knowledge exchange and share best practices to deepen understanding of the complex and multidimensional nature of climate change. This inaugural publication sheds light on varied and contextual experiences of Southeast Asian urban communities in addressing climate challenges and scenarios for future policy making.